Հայաստանի առաջին հանրապետության մամուլը - Ղազարյան, Հայկանուշ (Հայաստանի ազգային գրադարան)
The First Republic of Armenia initiated a series of activities for building Statehood and its legislative and executive bodies. Periodiclas were playing a crusial role in this process. At that time, in Armenian cities such as in Yerevan, Alexandrapolis, Goris, Kars, Echmiadzin 50 titles of periodicals representing Government, political parties, professional organizations, youth and education were published. Some of these periodicals are preserved in the collections of the National Library of Armenia, some in other organizations; suc as in the National Archives, in the Repository of the Ancient Manuscripts - Matenadaran, in the Museum of Literature and Art Towards 100th Anniversary of its First Republic the National Library of Armenia has initiated digitization of periodicals of the First Republic, and the digital surrogates are available from the database http://tert.nla.am.
Keywords: Մամուլի պատմություն; Մշակութային ժառանգություն